Preoperative Dural Contact and Recurrence Risk After Surgical Cavity Stereotactic Radiosurgery for Brain Metastases: New Evidence in Support of Consensus Guidelines - Susko, Matthew (Adv Radiat Oncol, 2019)
PURPOSE: The incidence of brain metastases is increasing as a result of more routine diagnostic imaging and improved extracranial systemic treatment strategies. As noted in recent consensus guidelines, postoperative stereotactic radiosurgery (SRS) to the resection cavity has lower rates of local control than whole brain radiation therapy but improved cognitive outcomes. Further analyses are needed to improve local control and minimize toxicity. METHODS AND MATERIALS: Patients receiving SRS to a resection cavity between 2006 and 2016 were retrospectively analyzed. Presurgical variables, including tumor location, diameter, dural/meningeal contact, and histology, were collected, as were SRS treatment parameters. Patients had routine follow-up with magnetic resonance imaging, and those noted to have local failure were further assessed for the recurrence location, distance from the target volume, and dosimetric characteristics. RESULTS: Overall, 82 patients and 85 resection cavities underwent postoperative SRS during the study period. Of these, 58 patients with 60 resection cavities with available follow-up magnetic resonance imaging scans were included in this analysis. With a median follow-up of 19.8 months, local recurrence occurred in 12 of the resection cavities for a 15% 1-year and 18% 2-year local recurrence rate. Pretreatment tumor volume contacted the dura/meninges in 100% of cavities with recurrence versus 67% of controlled cavities (P = .025). A total of 5 infield, 5 marginal, and 4 out-of-field recurrences were found, with a median distance to the centroid from the target volume of 3 mm. The addition of a 10-mm dural margin increased the target volume overlap with the recurrence contours for 10 of the 14 recurrences. CONCLUSIONS: Dural contact was associated with an increased rate of recurrence for patients who received SRS to a surgical cavity, and the median distance of marginal recurrences from the target volume was 3 mm. These results provide evidence in support of recent consensus guidelines suggesting that additional dural margin on SRS volumes may benefit local control.